(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article considers the problem of competences related to the willingness to implement prevention among students of universities. Distribution of youth extremism is one of the most acute problems of modern Kazakhstan.A growing number of crimes, the violence level increases, and its character become more organized. One of the key directions of the fi ght against terrorist extremist manifestations in society is their prevention. The ability of the organization of anti propaganda extremism is necessary in educational institutions.Solution to this problem is the introduction into curricula of higher professional education topics, highlighting the problem of protection from anti propaganda religious extremism. The course «Religious studies» will enable young people to adequately assess socially dangerous situation, connected with the manifestations of this phenomenon, to use necessary forms of psyche control in the case of manipulating the minds of people, the victims of religious organizations and totalitarian direction cults. Key words: extremism, skills, young people, elective courses, educational program, Religious Studies, typology of the destructive religious organizations.